A receptor for the complement regulator factor H increases transmission of trypanosomes to tsetse flies - Olivia J. S. Macleod (Nature Portfolio, 2020)
African trypanosome infections can persist for years, but immune evasion mechanisms are not fully understood. Here, Macleod et al. identify a trypanosome receptor for mammalian factor H, a negative regulator of the alternative complement pathway, that increases parasite transmission to tsetse flies.